PENGARUH RANGSANGAN DALAM TOKO TERHADAP PEMBELIAN YANG TIDAK DIRENCANAKAN OLEH KONSUMEN ALFA GUDANG RABAT DI DENPASAR - Andi Sularso (EKUITAS (Jurnal Ekonomi dan Keuangan), 2003)
This Research meant to know excitement factors in shop (In Store Stimuli) either through and also simultan ofparsial influencing purchasing which do not planning by consumer in Shop Alpha Warehouse Rabat in Denpasar. Data the used is primary data, namely data which in obtaining from result of propagated kuesioner. Unit analyse is consumer doing/conducting purchasing which do not be planned previously.Pursuant to result of analysis can be concluded that independent variabel which used have influence which significant either through and also simultan of parsial (except X5 variabel, namely service of salesgirl, what even have an effect on but do not signifikan) to pur chasing which do not be planned. Independent variabel which have an effect on biggest is variabel perception of consumer Lo settlemenL of shop rack, followed to be to be displayed by product, price and tidiness of product.  Perception of consumer medium to service of salesgirl, even have an effect on but do not signifikan.